(untitled) (PEDAGOGIC: Indonesian Journal of Science Education and Technology, 2026)
This study aims to develop an Augmented Reality (AR)-based learning media for the Science subject on the Solar System topic for eighth-grade students at SMP Muhammadiyah 5 Padang and to determine the validity and practicality of the developed media. This study employed a Research and Development (R&D) method using the 4-D development model, consisting of the stages of Define, Design, Develop, and Disseminate. The product was developed using three-dimensional objects that can be displayed through Android smartphones with the support of marker cards. Data were collected through validation questionnaires completed by media and material experts, as well as practicality questionnaires administered to students. The results showed that the Augmented Reality learning media obtained a 97.14% media validity score, categorized as very valid, while the material validity score reached 100%, also categorized as very valid. The practicality test resulted in a percentage of 94.48%, categorized as very practical. Therefore, the Augmented Reality-based learning media for the Solar System topic is considered very valid and very practical and can be used as an alternative learning medium for science instruction for eighth-grade students at SMP Muhammadiyah 5 Padang.